Marketing Management Development Strategy of SMP Muhammadiayah 3 Kutorejo Based on The Delta Model: Strategi Pengembangan Manajemen Pemasaran SMP Muhammadiayah 3 Kutorejo Berbasis The Delta Model - Nafiudin, Mokhammad; Rindaningsih, Ida (Indonesian Journal of Innovation Studies, 2026)
General Background: Islamic educational institutions face increasing competition and changing community needs, requiring structured marketing management. Specific Background: SMP Muhammadiyah 3 Kutorejo experiences fluctuations in new student enrollment amid competition from surrounding schools. Knowledge Gap: The school requires a structured marketing development approach that addresses product, customer, and relationship dimensions. Aims: This study formulates a marketing management development strategy using The Delta Model and identifies related challenges and opportunities. Results: Using an exploratory descriptive qualitative approach through interviews, observations, and documentation, the study identifies three strategic pillars: Best Product, Total Customer Solution, and Lock-In. Challenges include diverse student input, resource requirements, competition, economic conditions, and public concerns regarding Muhammadiyah, while opportunities include flagship programs, optimal services, social media publication, and community relationships. Novelty: The study applies the three-pillar framework to the specific context of SMP Muhammadiyah 3 Kutorejo. Implications: Integrated implementation supports planned promotion, quality programs, customer relationships, and a sustainable educational ecosystem. Key Findings Highlights Best Product integrates Qur’anic learning, tahfidz, religious activities, and inclusive education. Customer-oriented services address parents’ educational needs through involvement and quality services. Alumni networks, social media, and partnerships support long-term community relationships. Keywords : Development Strategy, Marketing Management, The Delta Model, Educational Marketing, Customer Relationship